PENGARUH DEBT TO EQUITY RATIO, DEBT TO ASSET RATIO, DAN CURRENT RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amelia Putri; Hamida Sari Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study was conducted to determine the effect of Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Current Ratio (CR) on Return on Assets (ROA) in Transportation and Logistics Companies Listed on the Indonesia Stock Exchange. The population in this study was Transportation and Logistics Companies Listed on the Indonesia Stock Exchange. The sample was taken using purposive sampling, resulting in 36 observations. Using multiple linear regression, classical assumption testing, simultaneous testing (F-test), and partial testing (t-test). The results of this study indicate that the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Current Ratio (CR) simultaneously have no effect on Return on Assets (ROA), with a calculated F value < F-table (1.907 < 2.90). The partial test results show that the DER, DAR, and CR variables do not affect ROA, as the DER significance value is 0.052 > 0.05 and the calculated t value (2.016) < t-table (2.03452). The DAR variable has a partial significance value of 0.068 > 0.05, with a calculated t value of -1.892 < -t-table (-2.03452). The CR variable has a partial significance of 0.591 > 0.05, with a calculated t-value (-0.543) < t-table (-2.03452). The Adjusted R-Square value, or coefficient of determination, is 0.072. This means that 7.2% of the variation or change in Return on Assets is explained by variations in the Debt to Equity Ratio, Debt to Asset Ratio, and Current Ratio, while 92.8% is influenced by other variables outside the research model.   Keywords: Debt to Equity Ratio, Debt to Asset Ratio, Current Ratio, and Return on Assets   Abstrak: Penelitian ini dilakukan untuk mengetahui apakah pengaruh Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), dan Current Ratio (CR) terhadap Return On Asset (ROA) Pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia. Populasi dalam penelitian ini adalah Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia. Sampel yang diambil dengan menggunakan purposive sampling, sehingga diperoleh 36 pengamatan sebagai sampel. Dan menggunakan metode regresi linier berganda, uji asumsi klasik, uji simultan (uji F) dan uji parsial (uji t). Hasil penelitian ini menunjukkan bahwa Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), dan Current Ratio (CR) secara simultan tidak berpengaruh terhadap Return On Asset (ROA) diperoleh nilai Fhitung < Ftabel (1,907<2,90). Hasil uji parsial variabel DER, DAR, dan CR tidak berpengaruh terhadap ROA karena nilai signifikan DER sebesar 0,052> 0,05 dan thitung (2,016) < ttabel (2,03452). Variabel DAR secara parsial memiliki signifikan sebesar 0,068> 0,05 dengan nilai -thitung (-1,892) < -ttabel (-2,03452). Variabel CR secara parsial memiliki sinifikan sebesar 0,591 > 0,05 dengan nilai -thitung (-0,543) < -ttabel (-2,03452). Nilai Adjusted R Square atau koefisien determinasi adalah 0,072. Hal ini berarti 7,2% variasi atau perubahan dalam Return On Asset dijelaskan oleh variasi Debt to Equity Ratio, Debt to Asset Ratio, dan Current Ratio 92,8 % dipengaruhi oleh variabel variabel lain diluar model penelitian.   Kata Kunci: Debt to Equity Ratio, Debt to Asset Ratio, Current Ratio dan Return On